2010
DOI: 10.4314/jasem.v12i2.55518
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm infection in Amassoma Community in the Niger Delta, Nigeria

Abstract: Studies on hookworm infection was conducted in Amassoma community, in the Niger Delta of Nigeria. Of the 4990 faecal samples examined by standard parasitological technique, 1740 (34.9%) samples were found to contain eggs of hookworm. Nine hundred and seventy five infected samples (33.6%) were males and 865 (36.7%) infected samples were females. Incidence or new cases of hookworm infection occurred every month. Highest incidence (12.2%) occurred in September and the lowest (1.8%) was in February. The high soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
0
0
Order By: Relevance
“…However, the observed significant association of hookworm infection with males verifies a previous account of a clear sex bias in hookworm infections in Nigeria. (Agi and Awi-waadu, 2008) and consistent with reports from African (Brooker, 2007) and Asia (Brooker et al, 2007 ;Jiraananku et al, 2011) countries where hookworm infections in males have been demonstrated to be more severe than in females. Significant association of gender with infection is in accordance with report of (El-Nadi et al, 2017;Heba et al, 2018) in Egypt who found that males were significantly infected than females.…”
Section: Discussionsupporting
confidence: 91%
“…However, the observed significant association of hookworm infection with males verifies a previous account of a clear sex bias in hookworm infections in Nigeria. (Agi and Awi-waadu, 2008) and consistent with reports from African (Brooker, 2007) and Asia (Brooker et al, 2007 ;Jiraananku et al, 2011) countries where hookworm infections in males have been demonstrated to be more severe than in females. Significant association of gender with infection is in accordance with report of (El-Nadi et al, 2017;Heba et al, 2018) in Egypt who found that males were significantly infected than females.…”
Section: Discussionsupporting
confidence: 91%
“…However, the observed significant association of hookworm infection with males verifies a previous account of a clear sex bias in hookworm infections in Nigeria. (Agi and Awi-waadu, 2008) [5] and consistent with reports from African (Brooker, 2007) [14] and Asia (Brooker et al, 2007;Jiraananku et al, 2011) [14,23] countries where hookworm infections in males have been demonstrated to be more severe than in females. Significant association of gender with infection is in accordance with report of (El-Nadi et al, 2017; Heba et al, 2018) [17,20] in Egypt who found that males were significantly infected than females.…”
Section: Discussionsupporting
confidence: 78%